Salafism And Religious Moderation: Reinterpreting Salafi Citizenship - Wafi, Mahmud Hibatul; Hidayati, Mega; Usman, Sunyoto; Jubba, Hasse (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study examines how and why Salafi groups, recognized for their puritanical and conservative ideologies, come to accept the concept of religious moderation. The objective of this research is to identify the factors that motivate Salafi groups to embrace religious moderation and to explore its impact on their religious identity and models of citizenship. Employing a qualitative-interpretative approach, this study utilizes data gathered from secondary sources, including books, articles, research reports, and social media The contribution of this study lies in providing a deeper understanding of how conservative religious groups can evolve and embrace more moderate discourse. This is particularly important in the current national context, as it fosters harmony and promotes religious tolerance. The findings indicate that Salafi groups accept religious moderation for various reasons, including social and political pressures, a desire for broader societal acceptance, and an evolving interpretation of their faith. However, this process is often challenging and frequently involves internal conflicts and struggles with identity. Salafi groups affirm their position as citizens by accommodating state policies, including the national religious moderation program. Their adaptation to the secular state system is crucial for their survival and influence within society.